Ormosia (Fabaceae: Faboideae) from the Miocene of southeastern China support historical expansion of the tropical genus in East Asia. (2nd December 2021) - Li, Xiang-Chuan; Manchester, Steven R.; Xiao, Liang; Wang, Qin; Hu, Yi; Sun, Bai-Nian
ABSTRACT: The development of the Asian monsoonal climate sparked a latitudinal shift in vegetation zones from the Oligocene to the Miocene. However, little is known about the history of the megathermal floristic response to the geologic events in key regions like subtropical China. Here, a species of Fabaceae, Ormosia cyclocarpa sp. nov., is recognised based on well-preserved fruits from the Miocene of Zhejiang in middle-subtropical China. This species features dehiscent, compressed suborbicular single-seeded pods with an intramarginal vein. Extensive comparisons with extant/fossil fabaceous taxa confidently support the present taxonomic consideration. Considering the extant distribution, diversity centre and regional climate history, the known fossil occurrences in southern China imply that Ormosia extended northwards during the Miocene from probable tropics of origin into subtropical China, where a once broad latitudinal arid zone prevailed throughout much of the Palaeogene. Such a changing phytogeographic pattern across tropical-subtropical China probably resulted from a drastic East Asian climate change around the Oligo-Miocene boundary, and closely coincided with the early-middle Miocene warming. The spreading of Ormosia and other tropical genera (e.g. Dipterocarpus, Shorea, Bauhinia, Dacrycarpus ) sharing similar floristic history in subtropical China indicates a palaeotropical and Miocene origin for some clades of the extant East Asian flora.